2015
DOI: 10.1007/s11046-015-9880-7
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Review of Published Reports on Primary Cutaneous Cryptococcosis in Immunocompetent Patients

Abstract: Primary cutaneous cryptococcosis (PCC) has been confirmed as a distinct clinical entity with secondary cutaneous cryptococcosis from systematic infection since 2003. Although it has been confirmed as a distinct clinical entity, little has progressed on PCC in immunocompetent hosts compared to their immunocompromised counterpart. We reviewed the literature on cases of PCC in immunocompetent patients from 2004 to 2014, and 21 cases from 16 reports were identified. Males are more likely to develop PCC infections,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0
7

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 27 publications
2
51
0
7
Order By: Relevance
“…Out of the ten cases which used fluconazole earlier, eight cases responded well to this therapy. Itraconazole was also found to be a good therapeutic option in these cases [31]. In our case, we found fluconazole therapy was effective in eliminating the infection.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Out of the ten cases which used fluconazole earlier, eight cases responded well to this therapy. Itraconazole was also found to be a good therapeutic option in these cases [31]. In our case, we found fluconazole therapy was effective in eliminating the infection.…”
Section: Discussionsupporting
confidence: 58%
“…In this context, we are describing these two strains as separate entities in this report. Primary cutaneous cryptococcosis is recognized as a distinct clinical entity since 2003 [31]. Primary cutaneous cryptococcosis cases were reviewed by Du et al recently who found 21 reported cases.…”
Section: Discussionmentioning
confidence: 99%
“…Primary cutaneous cryptococcal (PCC) infection has no pathognomonic presentation but presents most frequently as an asymptomatic or moderately itchy and painful nodule, cellulitis, or ulceration in exposed domains of the skin 4, 5. There were only 35 cases reported of PCC infection in immunocompetent individuals since 1966 4, 5.…”
Section: Discussionmentioning
confidence: 99%
“…At the end of the treatment, a complete re-epithelialization was obtained, even if scarring caused a partial inability to completely extend the last three fingers of the left hand (Figure 3). [15]. They were almost all elderly subjects and upper limbs were the most common site of infection.…”
Section: Case Presentationmentioning
confidence: 99%
“…Interestingly, itraconazole was effective in other seven cases reported by literature. Despite the efficacy of medical treatment, some patients needed surgical debridement to remove infected tissues and repair skin damages [15,16]. observed in other patients affected by PCC, diagnosis was delayed because of the absence of risk factors and other systemic symptoms.…”
Section: Case Presentationmentioning
confidence: 99%